ARBITRATION DISPUTE RESOLUTION MECHANISM IN FOREIGN INVESTMENT BASED ON INTERNATIONAL TRADE LAW - Yunita Novia Sari (Universitas Katolik Indonesia Atma Jaya, 2025)
Settling foreign investment disputes in Indonesia, in the context of increasing economic globalization, requires mechanisms that comply with applicable regulations to avoid inequalities between regulations for the disputing parties. Using a normative juridical approach and contextual methods, this study aims to understand the forms of foreign investment dispute resolution, including deliberation, Alternative Dispute Resolution (APS), litigation, and arbitration. The results indicate that arbitration is the primary option for resolving foreign investment disputes in Indonesia, due to the existence of specialized arbitration institutions such as BANI, ICSID, and UNCITRAL, as well as the recognition and enforcement of international arbitral awards that can be executed in other countries. This study concludes that arbitration is an effective and efficient dispute resolution mechanism for resolving foreign investment disputes in Indonesia.